(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
The search for deepening in specific areas has grown substantially in professional training, in order to investigate and share knowledge, together with active participation in practical activities, in order to preserve the inseparability of the teaching-research-extension tripod1 . Through this perception, strategies were adopted that promote immersion and articulation of knowledge between theory and practice, through the creation of Academic Leagues (AL), which consist of organizations characterized by their own statute, exempt from profit, composed of academics and oriented by professionals who are members of certain institutions, in an extracurricular manner.